Assessment of post-certification of ISO 14001 implementation in manufacturing industry in Malaysia - Tay, Hui Hui (2017)
Numerous studies have shown the benefits of ISO 14001 certification in terms of an organization’s operational and environmental management performance improvement. However, recent studies question the adoption of this voluntary EMS and the actual improvement achieved through the implementation and maintenance of ISO 14001. This study aims to assess the ISO 14001 post–certification implementation within Malaysia’s manufacturing industry. Assessments through identifying the direction and magnitude of the influences of study factors toward ISO 14001 post–certification conformance and investigating the factors that affect such conformance. A total of 186 respondents were selected from the more industrialized states of Selangor, Johor and Penang. A self-administered questionnaire and a follow up interview survey were employed for data collection. The data collected were discussed in terms of respondent profile, company profile and the measurement of study factors using a five point-likert scale. The study factors, including human resources and budget, competent person, top management commitment and perceived benefit, were found to have significant relationship with ISO 14001 compliance, except for management system certification experience. Results of the research provide input for manufacturing industries to improve their conformance level to achieve continual improvement with EMS ISO 14001 system.